Preparation and Characterization of Cellulose Acetate Butyrate/Organoclay Nanocomposites Produced by Extrusion - Guarda-Moraga, A; Rodriguez-Mercado, F; Galotto-Lopez, M (John Wiley and Sons Ltd, 2014)
Nanocomposite films based on cellulose acetate butyrate, modified montmorillonite (Cloisite® 30B), plasticizer (triethyl citrate) and antimicrobial compounds (carvacrol and cinnamaldehyde) were prepared by extrusion. The effects of the Cloisite® 30B content and antimicrobial compound types on the morphology of the nanocomposite films were investigated by X-ray diffraction and transmission electron microscopy. The thermal characteristics of films were analysed by thermogravimetry and differential scanning calorimetry; oxygen and water vapour permeability and tensile strength were determined. The film s antimicrobial behaviour against Listeria innocua, Staphylococcus aureus, Escherichia coli O157:O7 and Saccharomyces cerevisiae was investigated and determined using a viable cell count method. Nanocomposites with a Cloisite® 30B content of 3 wt% showed better dispersion than nanocomposites with a 5 wt% content. For films with antimicrobial compounds, tensile strength and Young s modulus decreased and water vapour permeability increased (150%) because of the plasticization effect of the antimicrobial compounds (essential oils). The nanocomposites with carvacrol and cinnamaldehyde were effective against the tested Gram-positive bacteria (reduction of at least 3.0 log CFU/ml) and yeast (reduction of at least 4.0 log CFU/ml). This study demonstrates that antimicrobial cinnamaldehyde and carvacrol can be successfully incorporated into cellulose acetate butyrate nanocomposites and that they have an inhibitory effect against microbial growth in solid medium. It shows the potential use of cellulose acetate butyrate for food packaging applications. © 2013 John Wiley & Sons, Ltd.